Environmental management system for small business: A case study at a shell petrol filling station, Dziyalite Resources Sdn. Bhd. / Eliyana Akram - Eliyana, Akram (2018)
Environmental challenges in today’s world can be exigent to some, especially for small business. Environmental management system is introduced to find balance between business and environment. Operation of a petrol filling station is an example of small business that has potential impact towards the environment and poses hazards to people. The focus of this study is to present, based on a case study, the feasibility of environmental management system adopted at a petrol filling station by identifying activities in the petrol station that potentially contributes to environmental issues along with potential risks associated to chemical and physical hazards at the premise. Data was collected through a walk-through observation technique and environmental management system assessment checklist that was adopted from the ISO 14001 standard besides interviews and discussions with the petrol station management. Establishment of an environmental aspect and impact register and setting up environmental indicators are suitable environmental approaches in order to improve environmental management on site. Other potential improvements are conduct 5S practice monthly to promote better housekeeping at store room, provide zebra crossing or signage at accident-prone area e.g. forecourt, provide designated recycling bins to promote 3R practices and investing rainwater harvesting system to reduce cost on water consumption. Overall, most of the activities that have impact to environment and risks are being well-managed by the petrol station’s management through various preventive controls as stipulated in their internal guideline. Future work recommendations could focus on gathering perception of environmental management system among petrol station workers and identification and evaluation of significant environmental impact from petrol station activities. Keywords: small and medium enterprises (SME), environmental management, environmental management system (EMS), petrol filling station, physical chemical risk.